(untitled) (Journal of history, 2025)
Despite Soviet society’s closed nature, the USSR’s population was characterized by a high degree of internal migration. The borders between Soviet republics never served as barriers to migration, functioning solely as administrative boundaries. The study of the challenges faced by Kazakh refugees returning from Central Asian republics in the 1930s contributes to understanding the degree of control over migration processes in the USSR and identifying the main reasons for reverse migration. This article aims to analyze the socio-economic prerequisites for addressing the migration of Kazakhs to the Central Asian republics and their return during the period of economic modernization in the USSR. The research relies on primary and secondary materials from libraries and archives. Documentary sources discovered in the archives of post-Soviet states, many of which have yet to be introduced into academic circulation, have become the primary resources for studying the history of the reverse migration of Kazakhs from the Central Asian Soviet republics. The issue of refugeehood and reverse migration are considered an integral part of the program developed by Soviet authorities to modernize the country’s socio-economic system. Forced collectivization was accompanied by the coerced transition of nomadic households to a sedentary lifestyle. Deprived of a significant portion of their livestock, the nomads disrupted their migration patterns by fleeing beyond the borders of Kazakhstan. The internal migration process during the Soviet period was characterized by large-scale population movements, both voluntary and forced, driven by economic and administrative policies aimed at meeting the demand for labor in the industrializing economy.